2013
DOI: 10.3389/fpls.2013.00083
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Rice Genes Closely Related to the ArabidopsisIRX9, IRX9L, and IRX14 Genes and Their Roles in Xylan Biosynthesis

Abstract: Xylan is the second most abundant polysaccharide on Earth, and represents a major component of both dicot wood and the cell walls of grasses. Much knowledge has been gained from studies of xylan biosynthesis in the model plant, Arabidopsis. In particular, the irregular xylem (irx) mutants, named for their collapsed xylem cells, have been essential in gaining a greater understanding of the genes involved in xylan biosynthesis. In contrast, xylan biosynthesis in grass cell walls is poorly understood. We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 68 publications
4
56
0
2
Order By: Relevance
“…Although recent studies using Arabidopsis mutants with a defective xylan structure showed that several GT43s and GT47s are specifically involved in the synthesis of the xylan backbone (Brown et al 2007;Lee et al 2010;Oikawa et al 2010;Wu et al 2010;York and O'Neill 2008). Bioinformatics approaches and mutant analyses suggested that several genes in the GT43, 47, and 61 families are potentially involved in AX synthesis (Anders et al 2012;Chiniquy et al 2012Chiniquy et al , 2013Mitchell et al 2007). Mitchell et al (2007) also suggested that the members of the PF02458 family, which is one of the subclades of benzylalcohol O-acetyltransferase (BEAT), anthocyanin O-hydroxycinnamoyltransferase (AHCT), anthranilate N-hydroxycinnamoyl/benzoyltransferase (HCBT), deacetylvindoline 4-O-acetyltransferase (DAT) (BAHD) acyltransferase family, might act as AX hydroxycinnamoyl transferases.…”
Section: Other Cell Wall-related Genesmentioning
confidence: 99%
“…Although recent studies using Arabidopsis mutants with a defective xylan structure showed that several GT43s and GT47s are specifically involved in the synthesis of the xylan backbone (Brown et al 2007;Lee et al 2010;Oikawa et al 2010;Wu et al 2010;York and O'Neill 2008). Bioinformatics approaches and mutant analyses suggested that several genes in the GT43, 47, and 61 families are potentially involved in AX synthesis (Anders et al 2012;Chiniquy et al 2012Chiniquy et al , 2013Mitchell et al 2007). Mitchell et al (2007) also suggested that the members of the PF02458 family, which is one of the subclades of benzylalcohol O-acetyltransferase (BEAT), anthocyanin O-hydroxycinnamoyltransferase (AHCT), anthranilate N-hydroxycinnamoyl/benzoyltransferase (HCBT), deacetylvindoline 4-O-acetyltransferase (DAT) (BAHD) acyltransferase family, might act as AX hydroxycinnamoyl transferases.…”
Section: Other Cell Wall-related Genesmentioning
confidence: 99%
“…Among these, AtIRX9 and AtIRX14 (both GT43 family members) and AtIRX10 (GT47), as well as their functionally redundant homologs, are believed to be involved directly in xylan backbone biosynthesis and to form a complex in the GA (Rennie and Scheller 2014). Orthologs of the AtIRX proteins have been identified in many other species, including wheat (Zeng et al, 2010), Populus trichocarpa (Lee et al, 2012b), Physcomitrella patens (Hörnblad et al, 2013), Plantago ovata (Jensen et al, 2013), rice (Oryza sativa; Chen et al, 2013;Chiniquy et al, 2013), Gossypium hirsutum , Neolamarckia cadamba (Zhao et al, 2014), and garden asparagus (Asparagus officinalis; Song et al, 2015). Enzymes involved in xylan backbone biosynthesis as well as side chain decorations, such as the arabinosyltransferases, glucuronosyltransferases, and acetylation enzymes, were recently reviewed by Rennie and Scheller (2014) and Hao and Mohnen (2014).…”
mentioning
confidence: 99%
“…To verify this finding in planta, we performed Suc density gradient centrifugation and western blotting of fractions prepared from wild-type seedlings. The fractions labeled by anti-OsTBL1/2 antibodies were largely identified by anti-IRX14 antibodies that recognize IRX14, a Golgi-protein involved in xylan biosynthesis in rice (Chiniquy et al, 2013;Lee et al, 2014), suggesting that OsTBL1 and IRX14 are present in the same organelle (Fig. 5C).…”
Section: Ostbl1 Is a Golgi-localized Proteinmentioning
confidence: 99%